STRATEGY FOR INCREASING THE COMPETITIVENESS OF SMEs IN THE ERA OF SOCIETY 5.0 - Hendra Dwi Prasetyo (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The emergence of Society 5.0 has ushered in a new era of heightened competition, urging Micro, Small, and Medium Enterprises (MSMEs) to navigate challenges creatively across realms spanning product innovation, marketing, product packaging, human resource development, and technology adoption. This study aims to delve into comprehensive strategies tailored to bolster the competitiveness of MSMEs within the context of Society 5.0. With a primary focus on countering the intensified competition induced by this paradigm shift, the research investigates key facets including product innovation, marketing strategies, product presentation, workforce development, and technological integration. Employing a qualitative research methodology grounded in literature study, this research endeavors to unravel potent strategies capable of equipping MSMEs with the tools not only to withstand but also to excel within the dynamic landscape of Society 5.0. By examining these strategies through the lens of qualitative analysis, this study contributes valuable insights for MSMEs seeking to thrive amidst the transformative currents of Society 5.0, fostering sustainable growth and resilience in an era characterized by unprecedented competition and innovation.